Myocardial infarction and death findings from a 22-year follow-up of a cohort of 980 employed Swedish men. (October 2019) - Dimberg, L.; Eriksson, B.; Hashem, M.
Abstract: Objectives: In this article, we present death and myocardial infarction (MI) incidences over 22 years in relation to possible risk factors and their explanatory value. Study design: In 1993, 980 middle-aged Swedish men in an automotive industry were surveyed at a health checkup as part of the Renault-Volvo Coeur project. The Swedish cohort was revisited in 2015. Methods: In 2015, incident MIs were identified using postal questionnaires, hospital records, and the Swedish national MI and death registers. The statistical results were given as odds ratios (ORs) and pseudo-R 2 (PR 2 ), showing the proportion of variation in risk explained by logistic models. Results: One hundred and four deaths (4.6 per 1000 person-years) and 89 first MIs (4.2 per 1000 person-years) were identified. The Framingham risk index showed the strongest association with MI (OR = 23; 95% confidence interval [CI] = 5.42, 96.9), comparing the fifth quintile with the first. The all-cause death showed an OR of 3.2 (95% CI = 1.65, 6.08), with a suggested U-shape over quintiles. The percentages of PR 2 for MI and death were 8.8% and 6.6%, respectively. All risk factors together explained 22% of the variation in risk of MI. Comparing mortality in men living alone with those married yielded an OR of 3.78, which was found to be statistically significant. The corresponding OR for MI was not significant. Conclusions: Traditional risk factors were confirmed but explained a modest proportion of the risk variation. Highlights: The Framingham risk index stands out to have the strongest explanatory capacity of the risk variation for myocardial infarction (MI) and death of the variables studied. Other strong explanatory factors for MI were smoking and diabetes. The odds ratios (ORs) for three anthropometric measures, body mass index, waist-hip ratio, and sagittal diameter divided by height, were all significantly associated with MI and death, but with no significant preference. Living single meant significantly higher risk of death compared with being married (OR = 3.8), but the risk of MI was non-significant (OR = 1.1). Traditional risk factors explained merely 22% of the variation of MI.